Rating and rewarding higher education for sustainable development research within the marketised higher education context: experiences from English universities. Issue 4 (3rd April 2019) - Bessant, Sophie E. F.; Robinson, Zoe P.
Abstract: This paper explores one key aspect of marketisation in English universities, the quality-related research funding (QR) system, which central government in the United Kingdom uses to allocate funds to Higher Education Institutions (HEIs), based on a system of reviewing and rating the 'quality' of research at different HEIs. Specifically, it focuses on the experiences of 30 members of academic staff from eight universities across England who were engaged in research and/or scholarly activity in the broad field of Higher Education for Sustainable Development (HESD), during the time leading up to the 2014 Research Excellence Framework (REF) submission period. Interviewees were asked to talk about their experiences of being a HESD researcher/scholar within the context of the QR system and their perceptions of the relationship between the QR system and interdisciplinary, sustainability, pedagogic and HESD research. Findings from the semi-structured interviews and resulting qualitative analysis, reveal a number of obstacles facing HESD researchers which are outlined and explored in the paper. Strategies and rationale for improving the quality, reputation and ultimately, the 'REF-ability' of HESD research are discussed, and highlight the complex interface between marketisation and sustainability in higher education.